SCREENING OF COTTON (GOSSYPIUM HIRSUTUM L.) GERMPLASM AGAINST COTTON LEAF CURL VIRUS (CLCUV) - NASEER, S; KHALID, K; MARYAM, B; BHATTI, AM; MANAN, A; FAISAL, M; SHERAZ, M; IQBAL, J; AMEEN, M; JAVED, MHB (Biological and Clinical Sciences Research Journal, 2024)
Cotton Leaf Curl Virus (CLCuV) is a devastating disease affecting cotton production worldwide, particularly in South Asia and Africa transmitted by the whitefly (Bemisia tabaci). CLCuV infection leads to severe symptoms, including leaf curling, vein thickening, stunted growth, and significant yield losses. Developing resistant cotton varieties is the most suitable strategy for managing CLCuV, given the limitations and environmental concerns associated with chemical controls. This study aimed to evaluate the resistance and susceptibility of different cotton varieties to CLCuV under natural field conditions and artificially infected condition using a disease severity scale ranging from 0 (highly resistant) to 5 (susceptible). A total of five cotton varieties, were assessed at three critical growth stages: vegetative, flowering, and boll formation. Disease severity, and yield components were recorded to determine extent of resistance of each variety. The results indicated that genotypes and treatments had significant variation in control compared to T1. According to DSI, NIAB-852 was scored as resistant with 10% infected leaves. FH-142 and CIM-496 were scored as tolerant according to DSI with 10-25% infection in leaves. NIAB Karishma and CIM-448 were scored as moderately susceptible with 50-75% infection. All genotypes had significant reduction in number of bolls, boll weight and seed cotton yield in T1 than control. These findings provide valuable insights into the effectiveness of existing cotton germplasm against CLCuV and highlight the need for continuous evaluation and development of resistant varieties. The study highlights the importance of generating resistant cultivars, thereby ensuring sustainable cotton production.